EVALUATION OF THERAPEUTIC EFFICACY OF ALOE VERA GEL FOR EXCISIONAL WOUND HEALING MECHANISM USING ANIMAL MODEL - PERVEEN, A; ABBAS, S; KHAN, SU; MAZHAR, M; FIAZ, A (Biological and Clinical Sciences Research Journal, 2023)
Wound-healing diseases are considered significant clinical issues in patients, which become more complicated in association with obesity, diabetes mellitus, and high blood pressure conditions. Various therapeutic options were available for the wound-repairing process. The current study project evaluated the healing properties of Aloe Vera gel on epidermal wounds in rats. Experimental animals (adult rats) were divided into groups A, B, and C with equal distribution. These groups represent treatment, without treatment, and control, respectively. A pair of wounds measuring 2cm x 2cm each was created hygienically on the back of each rat lateral to the spinal cord. The wounds were treated with homogenized Aloe Vera gel, while the injuries in the second group were treated with normal saline. Blood samples were collected on days 21 for hematology analysis with a standard method. Animals in group ‘A’ had significantly faster healing with shorter days of skin fall-off than the control and untreated group. Further biochemical changes in the packed cell volume, mean corpuscular volume, lymphocyte and neutrophil counts also showed significant results compared to the control group. The study concluded that Aloe Vera effectively treated epidermal wounds in adult rat models. An improvement occurred in the hematological profile of the experimental animals. These findings will go a long way in expanding the horizon of the clinical application of this plant in solving wound-healing problems in humans and other animal species.